Role of UDP-glucose ceramide glucosyltransferase in venous malformation - Chen, Sheng; Wang, Yuan; Kong, Liangliang; Ji, Yi; Cui, Jie; Shen, Weimin (Frontiers in Cell and Developmental Biology, 2023)
Venous malformation (VM) results from the abnormal growth of the vasculature; however, the detailed molecular mechanism remains unclear. As a glycosyltransferase, UDP-glucose ceramide glucosyltransferase (UGCG) is localized to the Golgi body and is a key enzyme in the first step of glycosphingolipid synthesis. Here, we aimed to explore the relationship between UGCG and the development of VM. First, investigations using RT-qPCR and western blotting on the diseased vasculature of VM patients and normal vascular tissues revealed that UGCG expression was markedly elevated in the diseased vessels. Subsequently, immunofluorescence assay showed that UGCG was co-localized with CD31, an endothelial cell marker, in tissues from patients with VM and healthy subjects. Then, we established TIE2-L914F-mutant human umbilical vein endothelial cells (HUVECs) by lentivirus transfection. Next, western blotting revealed that UGCG expression was considerably higher in HUVECsTIE2-L914F. In addition, we established a UGCG-overexpressing HUVEC line by plasmid transfection. With the CCK8 cell proliferation experiment, wound healing assay, and tube formation assay, we found that UGCG could promote the proliferation, migration, and tube formation activity of HUVECs, whereas the inhibition of UGCG could inhibit the proliferation, migration, and tube formation activity of HUVECsTIE2-L914F. Finally, western blotting revealed that UGCG regulates the AKT/mTOR pathway in HUVECs. These data demonstrated that UGCG can affect the activity of vascular endothelial cells and regulate the AKT/mTOR signaling pathway; this is a potential mechanism underlying VM pathogenesis.